Pendampingan Kampung Pendidikan Kampung’e Arek Suroboyo (Kp Pas) RW 03 Kelurahan Ketintang Surabaya - Mochamad Mochklas; Zeni Rusmawati; Aris Santoso; Roudotul Jannah (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
Education Village of Kampung'e Arek Suroboyo (KP KAS) is one of the efforts to make the village in Surabaya feasible for children's growth and development. Help from the assistance of Education Village of Kampung'e Arek Suroboyo (KP KAS) in RW 03 Ketintang, so that the residents of Ketintang Baru can make a portfolio of an educational village, a village that is comfortable and safe for the process of growth and development. The participation of all components of the Ketintang residents RW 03 that will make this program successful. With the awareness and concern of the citizens of RW 03 Ketintang managed to become a village of education, a village that guarantees the development of children in a comprehensive manner both spiritual, intellectual, social emotional, and physical aspect